Draft Annual Plan Andhra Pradesh 1994-95 Volume-II (Sectoral Programmes) 3. Irrigation and Flood Control - Planning Commission (Planning Commission, 1994)
Irrigation is the major input for Agriculture and it has been the endeavour of the State to provide sufficient funds for sustained development of this infrastructure. Priority has been given to provide adequate funds for ongoing projects while exercising restraint in starting new projects. Emphasis was also placed on execution of projects taken up under external aid to avoid cost escalation.
Finance and Planning (PLG. Wing) Department, Government of Andhra Pradesh